1994
DOI: 10.1111/j.1600-0447.1994.tb01548.x
|View full text |Cite
|
Sign up to set email alerts
|

The middle‐aged generation is at high risk for suicide in Japan

Abstract: The suicide rate in Japan was the highest in the world the 10 years after World War II. There were many suicides among young and aged people. Now, Japan has many suicides among middle-aged people, and suicides among elderly people are still remarkable. These findings suggest that middle-aged people in 1980s have a high risk of suicide and that suicide among elderly people will increase in 10-20 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…1 As in many other countries, elderly suicide is an important public health issue, those 70 years of age and older having the highest suicide rate. [2][3][4][5][6] Suicide rates vary regionally, [7][8][9][10][11][12][13][14][15] and among Canadian provinces British Columbia had the highest suicide rate at the time of a national overview. 16 Among many factors with potential influence, season and weather effects are of interest.…”
mentioning
confidence: 99%
“…1 As in many other countries, elderly suicide is an important public health issue, those 70 years of age and older having the highest suicide rate. [2][3][4][5][6] Suicide rates vary regionally, [7][8][9][10][11][12][13][14][15] and among Canadian provinces British Columbia had the highest suicide rate at the time of a national overview. 16 Among many factors with potential influence, season and weather effects are of interest.…”
mentioning
confidence: 99%
“…In the present study, moreover, we found that in cases of middle‐aged or elderly suicide, hanging was used frequently rather than other methods such as falling or drowning. The results of the aforementioned studies show that middle‐aged and elderly people have a higher risk for committing suicide in Japan 6,7,26 …”
Section: Discussionmentioning
confidence: 99%
“…Japanese government officials stated that the widening disparity was caused by a 40% rise in suicides among men, notably among middle‐aged men threatened with redundancy 5 . This tendency had been suggested by other studies since the early 1990s 6,7 . More recently, Aihara and Iki reported that the recent increase in the suicide rate in Japan was related to some socioeconomic factors, such as job applications and divorce 8,9 .…”
Section: Introductionmentioning
confidence: 88%
“…In Japan, a dramatic rise in a suicide rate was observed in the 1950s, and then the rate decreased just as rapidly in the 1960s [7, 8]. The rate in Japan was one of the highest worldwide in the 1950s [9].…”
Section: Introductionmentioning
confidence: 99%
“…The rate in Japan was one of the highest worldwide in the 1950s [9]. It has been suggested that this change may be associated with the traumatic or difficult experiences of Japanese people during and after World War II and socioeconomic factors, such as unemployment rates, in the 1950s and 1960s in Japan [7, 8, 10, 11]. Concerning suicide methods used frequently during these periods in Japan, Araki et al reported that suicide rates due to poisoning by solid and liquid substances in young people changed markedly in this period, and that these means were responsible for the rapid change [12].…”
Section: Introductionmentioning
confidence: 99%